Peran Pemberdayaan Kesejahteraan Keluarga dalam Penurunan Prevalensi Stunting di Kelurahan Kestalan, Kecamatan Banjarsari, Surakarta - Intan Dwi Agustina; Nurhadi Nurhadi; Dwi Astutik (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
Stunting is a condition where children fail to thrive which is caused by several factors so that it can affect a child's growth and development. Toddlers who experience stunting have bodies that are shorter than the standard height for children their age. The stunting figure in Surakarta City in 2019 shows that 1.35 percent of children aged under two years were stunted, this has decreased compared to the stunting percentage figure in 2018, which was 2.19%. This research will discuss the factors that cause stunting and efforts to reduce the prevalence of stunting in Kestalan Village, Surakarta through the role of empowering family welfare. Data collection techniques were carried out using in-depth interviews and documentation studies. Social action theory by Max Weber is used as an analytical tool to determine the relationship between variables from research results. The research results show that the cause of stunting in children in Kestalan Village, Banjarsari District, Surakarta City is parents' lack of knowledge regarding nutritional intake, lifestyle, congenital diseases, the environment, and most parents smoking. The government and the community have made various efforts to accelerate stunting reduction, one of which is through the contribution of the Family Welfare Empowerment Team (PKK). Efforts to reduce stunting can be carried out through the role of Family Welfare Empowerment (PKK), namely in health services, posyandu activities, collaboration with the government and the private sector in providing additional food assistance (PMT), counseling and assistance, education and motivation.